DEVELOPING A TUTORIAL MODEL INSTRUCTIONAL MEDIA DREAMWEAVER FOR WEB PAGE MANAGEMENT SUBJECT FOR THE XI GRADE STUDENTS MAJORING IN MULTIMEDIA AT SMK NEGERI 3 SINGARAJA - Tuning Somara Putra, Gd (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
Utilizing the science and technology to support the process of teaching and learning in activities is one of many positive impacts of technology. The development of information technology is one of the technology advancements which can be applied and exploited in developing the knowledge. However, in Web Page Management subject in SMK Negeri 3 Singaraja, the teacher in the process of teaching and learning faced a problem of transferring the material to the students. Thus, developing a tutorial model of teaching and learning media was a significant step to develop teaching equipment in which it offers a computerizestudents friendly material explanation, and question and feedback giver. Based on the problems faced in this study, the development of tutorial model of teaching and learning media by using Dreamweaver is compulsory in Web Page Management subject. There were several softwares used in making this program, namely: Macromedia Flash 8, Adobe Photoshop for editing the graphic, Cool Edit Pro 2 for editing the sound, Adobe Premiere Pro 1.5 and Camtasia 7 for editing video, Adobe Dreamweaver Cs3, Macromedia Dreamweaver, and Xampp as testing softwares. Dreamweaver tutorial instructional media models have different functions in each menu. Like the menu that contains the material subject matter, which has a video tutorial video, as a tool for teaching and evaluating students' abilities test equipment. From the test media of learning dreamwaver to the students, the results showed scattered on the category of student response was very positive 2.77%, 97.23% positive, enough 0%, 0% less positive and very less positive 0%. From the results of these studies are very positive student responses categorized.